An investigation of individual functionality football referees of high qualification - Chopilko, T. G. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to determine the level of individual functionality arbitrators of high qualification. Material: in the experiment participated 29 high qualification arbitrators aged 21-45 years.